Multidimensional signal, image, and video processing and coding - Woods, John W. (John William), 1943- (Amsterdam ; Boston : Academic Press, 2012)
Digital images have become mainstream of late notably within HDTV, cell phones, personal cameras, and many medical applications. The processing of digital images and video includes adjusting illumination, manufacturing enlargements/reductions, and creating contrast. This development has made it possible to take long forgotten, badly damaged photos and make them new again with image estimation. This fully revised and expanded second edition, will give you the necessary understanding of image and video processing concepts to contribute to this hot technology's future advances. Important new topics include introductory random processes, image enhancement and analysis, and the new MPEG scalable video coding standard. Only R & D level tutorial that gives an integrated treatment of image and video processing - topics that are interconnected. New chapters on introductory random processes, information theory, and image enhancement and analysis Coverage and discussion of the latest standards in video coding: H.264/AVC and the new scalable video standard (SVC).
Two-Dimensional Signals and Systems; Sampling inTwo-Dimensions; Two-Dimensional Systems and Z-transforms; 2-D Discrete Transforms; Two-Dimensional Filter Design; Introductory Image Processing; Image Estimation and Restoration; Digital Image Compression; Three-Dimensional Signals and Systems Properties of 3.D Fourier Transform, 3.D Filters, 3-D Sampling Theorem; Digital Video Processing; Digital Video Compression; Video Transmission over Networks.
Includes bibliographical references and index.
Keywords: Image processing -- Digital techniques; Signal processing -- Digital techniques; Video compression -- Standards; Digital video; COMPUTERS -- Information Theory; TECHNOLOGY & ENGINEERING -- Signals & Signal Processing; Digital video; Image processing -- Digital techniques; Signal processing -- Digital techniques; Video compression -- Standards